Datives in Nilotic in a typological perspective - Dimmendaal, Gerrit J. (AAeO - Afrikanistik-Aegyptologie-Online, 2009)
Amongst the set of widespread derivational extensions on verbs in Nilotic, there is one prototypically marking an event directed towards some individual or a location, usually referred to as the Dative marker in the study of this language family. The Nilotic family is commonly divided into three branches (following Köhler 1955): Western, Eastern, and Southern Nilotic, and the Dative suffix is attested in all three primary branches of this Nilo-Saharan subgroup. Since Dative marking in Nilotic languages involves the use of cognate morphemes, these distributional facts allow us – in principle – to trace down not only the formal but also the syntactic and semantic history of this verbal marker.